Sejarah dan Perkembangan Madrasah Aliyah Negeri 1 Ketapang - Akbar, Ahmad; Mahrus, Erwin (Jurnal Ilmiah Global Education, 2024)
Education plays a crucial role in shaping the future generations of both the nation and religion. The quality of education today holds paramount importance in human life. A nation's progress heavily relies on the quality of its education system. Madrasah, as educational institutions in Indonesia overseen by the Ministry of Religion, have evolved into modern Islamic educational establishments. Their modernization is evident in both their physical infrastructure and academic standards. Madrasah now boast comprehensive facilities to support academic development, competent educators with specialized knowledge, dedicated staff, and other essential resources. Moreover, they have clearly defined institutional visions, missions, and goals that guide curriculum development. Each madrasah exhibits unique strengths and opportunities, reflecting the diversity among educational institutions. The provision of facilities and resources is a crucial factor considered by educators when crafting curricula. Hence, madrasah, as institutions characterized by Islamic principles, must develop curricula that encompass scientific programs integrating religion, technology, and soft skills such as independence and leadership.